The Role Of The Police In Combating Terrorism Crimes - Gilang Gemilang; Yasmirah Mandasari Saragih; Mhd. Azhali Siregar; Askamaini Askamaini (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The existence of the police is essential in overcoming criminal acts of terrorism, because the police are structured in such a way from the regions to the center and are also in accordance with the duties and functions of the police in creating public security and enforcing the law. The problem raised in this research is: what are the steps taken by the National Police in tackling criminal acts of financing terrorism? What are the obstacles to the National Police in dealing with criminal acts of terrorism?This research is directed towards normative, or doctrinal, juridical legal research which is also referred to as library research or document study, because it is mostly carried out on secondary data in libraries. The results of the research and discussion explain the role of the National Police in overcoming criminal acts of terrorism, namely maintaining public security and order, which is a dynamic condition of society as one of the prerequisites for implementing the national development process in order to achieve national goals which are characterized by ensuring security, order and the rule of law, as well as fostering it. peace, which contains the ability to foster and develop the potential and strength of society in warding off, preventing and overcoming all forms of law violations and other forms of disturbance that can disturb society. The National Police's efforts to tackle terrorism include repressive efforts, preventive efforts and preemptive efforts. The obstacle for the National Police in tackling terrorism is that it is hampered by the synergy of cross-sectoral cooperation, namely between the police, regional government and other related agencies.